The origins, development and meaning of the figure Urizen in the poetry, prophecies and graphic art of William Blake - Larrissy, E; Larrissy, Edward T. (1980)
﻿ The thesis examines Urizen in relation to Blake's intellectual, religious and artistic background. The ideas of jealousy, possessiveness and the cruelties of Kings and Priests are already present in early Blake. These various kinds of restriction contribute to the notion of the 'bounded', the sources of which are traced to empirical philosophy, though it has a very wide reference in Blake. It is central to the meaning of Urizen, whose name probably derives from a Greek verb meaning 'to bound, limit'. But Blake also believed in firm outline. Is this not a limit? The difference between the two notions of 'bound' is examined, with reference to the Neoplatonists: the contrast is very close to that between the 'mechanic'and the 'organic'. Urizen develops in relationship with his antagonists, Ore and, more subtly, the Bard. Ore and Urizen are both described in terms of the serpent and Satanic imagery, which suggests that they are part of the same malaise. The Bard looks like Urizen, for the Priest derives from the Poet, as Blake would have learned from contemporary primitivist writers. Urizen, like the Priest, abstracts the Infinite from the world of Forms. The sources of this idea are to be found in Fludd and the Gnostics. The Ore-cycle finds its fullest expression in Vala. Blake may have thought of Urizen and Ore as the opposed poles of the cycle of Melancholy and Mania: Urizen owes much to the iconography of Saturn and Melancholy. It is this cycle of alternating and divided Reason and Energy which Blake now thinks the true evil: Satan the Selfhood. There are many alchemical sources for a divided Satan, such as we see in the guises of Urizen and Luvah in Illustrations of the Book of Job. But Blake also comes to value the qualities of a redeemed Urizen, who had always had the grandeur of the Creator about him. The Priest may become the Bard again, as in the Job illustrations; or to put it another way: the 'bounded' may become Living Form.